Effect of delayed light-curing on solubility, color stability, and opacity of Fuji II LC glass ionomer cement: original article - Nejatifard, Marzieh; Panahandeh, Narges; Ghasemi, Amir; Torabzadeh, Hassan (Brazilian Dental Science, 2022)
Objective: Resin-modified glass ionomer (RMGI) cements are among the commonly used restorative materials inlow stress-bearing areas and also for temporary restorations. The competition between acid-base reactions andlight polymerization reactions in delayed curing of RMGIs can affect their physical and mechanical properties,as well as their degree of conversion. Since solubility, color stability, and opacity are among the main physicalproperties affecting the durability and clinical service of RMGI restorations, this study aimed to assess the effectof delayed curing on solubility, color stability, and opacity of Fuji II LC RMGI. Material and Methods: This invitro, experimental study evaluated 80 Fuji II LC RMGI specimens (10 specimens per each in 4 groups) in termsof solubility, color stability, and opacity at 6 months later. Specimens were cured immediately or were curedwith 1, 5 and 10 min delay. Results: Maximum solubility and minimum change in opacity and color stabilityat 6 months were noted in the group with delayed curing by 10 min. A significant difference was noted in thesolubility of specimens cured after 10 min and 1 min. Significant differences were also noted in the opacity andcolor stability of specimens cured after 10 min and all other groups (P < 0.05). Conclusion: Delayed curingby 1 min decreased the solubility of RMGI specimens compared with immediate curing or curing after 5 min.Although this difference did not reach statistical significance. Color stability and changes in opacity are mainlyinfluenced by the acid-base reactions rather than polymerization reactions.KEYWORDSGlass Ionomer cement; Fuji II LC cement; Solubility; Color; Opacity.